Consolidation budget 1987 - Federal Republic of Nigeria (Lagos-Nigeria : Federal Government of Nigeria, 1987)
This paper discusses various components of the Nigeria government budget of consolidation under the Gen, Ibrahim Babangida regime. It encapsulates various revenue indices from agencies to ministries.
asm; 10/04/19
Loans
Keywords: Budget; Nigeria